KEBUTUHAN DAN PARTISIPASI MASYARAKAT DALAM PROGRAM KEMITRAAN DAN BINA LINGKUNGAN (PKBL) PTPN VII UNIT USAHA REJOSARI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Erisa Widyanti; Sumaryo Gitosaputro; Helvi Yanfika (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This study analyzes the community needs for PKBL in order to formulate the strategy of PKBL accordance with the community needs and their environment,  the level of community participation in PKBL, and the correlating factors to community participation in PKBL. This research was conducted in Rejosari Village, Natar Sub-district, South Lampung Regency.  The samples in this study were 84 households that was chosen randomly. The data was analyzed by descriptive qualitative analysis, tabulation, and Rank Spearman correlation. The results showed that the community needs for PKBL included a) economy aspect: the assets loan without interest for the community in three subvillages, training of biogas production in Banjar subvillage, cattle farmer’s group trainer in Northern and Southern Titirante subvillages, skill trainings, the market provisionand product promotion; b) social aspect: the development of institutional activities, the complement of educational facilities in three subvillages, and the construction of high school buildings in Rejosari Village; c) environmental aspect: asphalting roads and bridge repairment. In addition to d) health aspect: public health improvement programs through free medical check up service or health infrastructure improvement. The level of community participation in PKBL was low. The factors correlated to community participation in PKBL of PTPN VII were education level, the number of family members, and the length of staying. Key words: community, needs assesment, participation, PKBL, program